1998
DOI: 10.1091/mbc.9.10.2905
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Cellular Localization of the Cyclosporine A-sensitive Transcription Factor NF-AT in Skeletal Muscle Cells

Abstract: The widely used immunosuppressant cyclosporine A (CSA) blocks nuclear translocation of the transcription factor, NF-AT (nuclear factor of activated T cells), preventing its activity. mRNA for several NF-AT isoforms has been shown to exist in cells outside of the immune system, suggesting a possible mechanism for side effects associated with CSA treatment. In this study, we demonstrate that CSA inhibits biochemical and morphological differentiation of skeletal muscle cells while having a minimal effect on proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
229
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(251 citation statements)
references
References 46 publications
(47 reference statements)
19
229
2
Order By: Relevance
“…Together, these studies demonstrate that the early differentiation and diversification of cardiac myocytes is not dependent on calcineurin signal transduction. This finding is in contrast to the effects of CsA treatment or loss of CnA isoforms on the differentiation of cultured skeletal muscle myocytes and on the diversification of slow vs. fast skeletal muscle lineages (Abbott et al, 1998;Chin et al, 1998;Delling et al, 2000;Parsons et al, 2003). In general, calcineurin inhibition leads to loss of slow muscle fibers in cultured skeletal myocytes or genetically altered mice.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Together, these studies demonstrate that the early differentiation and diversification of cardiac myocytes is not dependent on calcineurin signal transduction. This finding is in contrast to the effects of CsA treatment or loss of CnA isoforms on the differentiation of cultured skeletal muscle myocytes and on the diversification of slow vs. fast skeletal muscle lineages (Abbott et al, 1998;Chin et al, 1998;Delling et al, 2000;Parsons et al, 2003). In general, calcineurin inhibition leads to loss of slow muscle fibers in cultured skeletal myocytes or genetically altered mice.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, cultured mouse embryos treated with CsA beginning at E8.5 exhibited a variety of malformations and embryonic growth retardation, supporting the requirement for calcineurin signaling at these later stages (Uhing et al, 1993). In cell culture experiments, CsA treatment inhibits the differentiation of skeletal and vascular smooth muscle cells and also inhibits contractile activity and calcium handling in cardiomyocytes (Abbott et al, 1998;Janssen et al, 2000;Robida et al, 2000;Ohkawa et al, 2003). Further studies are necessary to identify specific populations of cells in the embryo affected by calcineurin inhibition in vivo and to determine the timing of sensitivity of different cell lineages during development.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, it was shown that the inhibition of calcineurin by CsA induced extensive inflammation, marked fiber atrophy, and the appearance of immature myotubes in regenerating muscle compared with placebo-treated mice 60) . Several other studies indicated such defects in skeletal muscle regeneration when calcineurin was inhibited 62,63) , whereas transgenic activation of calcineurin is known to markedly promote the remodeling of muscle fibers after damage 50,64) .…”
Section: Insulin-like Growth Factor-i and Mapk (Proliferation Phase)mentioning
confidence: 99%
“…This phosphatase has been involved in muscle differentiation (Abbott et al, 1998), fiber type determination (Chin et al, 1998) and hypertrophy (Musaro et al, 1999). Calcineurin binds to and activates nuclear factor of activated T cells (NFAT) (Rao et al, 1997;Crabtree, 1999), which targets the nucleus, dimerizes with other nuclear factors and modulates transcription of target genes (Rao et al, 1997).…”
Section: Introductionmentioning
confidence: 99%